2013
DOI: 10.1016/j.telpol.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Does ICT in schools affect residential adoption and adult utilization outside schools?

Abstract: Policymakers around the world are considering whether to invest in putting information and communication technology (ICT) in schools, and how. While educational impact is likely to be the primary objective, such investments can also affect residential adoption and adult utilization of ICT in the communities, thereby reducing the digital divide. Using a census survey of Thailand for a time when ICT was available in roughly half of the nation's schools, this study employs logistic regression and propensity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Age, gender, race and language also explain some variance in the adoption of ICTs (e.g., Chaudhuri et al, 2005;Ono and Zavodny, 2007). Closer to our paper, Tengtrakul and Peha (2013) showed a positive correlation between availability of ICTs in schools and Internet household adoption in Thailand.…”
Section: Icts In Schools and In Householdssupporting
confidence: 46%
“…Age, gender, race and language also explain some variance in the adoption of ICTs (e.g., Chaudhuri et al, 2005;Ono and Zavodny, 2007). Closer to our paper, Tengtrakul and Peha (2013) showed a positive correlation between availability of ICTs in schools and Internet household adoption in Thailand.…”
Section: Icts In Schools and In Householdssupporting
confidence: 46%
“…Caselli and Coleman's (2001) study of computer diffusion found evidence that the attainment of secondary education and imports per worker strongly increases computer diffusion. More recent work by Cruz-Jesus, Oliveira, and Bacao (2012), Cruz-Jesus et al (2016), and Tengtrakul and Peha (2013) confirms the importance of school education for ICT adoption. Conversely, Chinn and Fairlie (2007) found no significant relationship between education and Internet diffusion, but highlighted the importance of telecommunication regulatory policy as a determinant of Internet diffusion.…”
Section: Literature Reviewmentioning
confidence: 78%
“…Tengtrakul and Peha [32] focused on whether the use of ICTs in schools affected residential adoption and adult utilization outside schools. The study was based on the SchoolNet project in Thailand, which supported the provision of Internet access to schools.…”
Section: Organization/authorsmentioning
confidence: 99%